Resolving Nonperforming Loans in Sub-Saharan Africa in the Aftermath of the COVID-19 Crisis - Eyraud, Luc (Departmental Papers; Departmental Paper ;, 2021)
Sub-Saharan African countries are facing an unprecedented health and economic crisis that is likely to severely hurt credit quality and raise non-performing loans from already high levels. Banks have a critical role to play not only during the crisis by providing temporarily relief to businesses and households, but also during the recovery by supporting economic activity and facilitating the structural transformations engaged by the pandemic.